2016
DOI: 10.1098/rspb.2016.0150
|View full text |Cite
|
Sign up to set email alerts
|

Treating cattle with antibiotics affects greenhouse gas emissions, and microbiota in dung and dung beetles

Abstract: Antibiotics are routinely used to improve livestock health and growth. However, this practice may have unintended environmental impacts mediated by interactions among the wide range of micro-and macroorganisms found in agroecosystems. For example, antibiotics may alter microbial emissions of greenhouse gases by affecting livestock gut microbiota. Furthermore, antibiotics may affect the microbiota of non-target animals that rely on dung, such as dung beetles, and the ecosystem services they provide. To examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 65 publications
8
72
1
2
Order By: Relevance
“…Although the impact of livestock management on dung beetle assemblages seems to be weaker than that of landscape structure, the use of macrocyclic lactones is strongly and negatively related to all response variables. This supports previous work showing that macrocyclic lactones have negative effects on the ecology and biology of different soil invertebrate taxa, including mites, springtails, earthworms, flies, wasps (Hammer et al., ; Jochmann & Blanckenhorn, ) and dung beetles (Basto‐Estrella et al., ). These negative effects are related to the accumulation of macrocyclic lactones in cattle dung, changing their nutritional, chemical and microbiological properties (Hammer et al., ; Jochmann & Blanckenhorn, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although the impact of livestock management on dung beetle assemblages seems to be weaker than that of landscape structure, the use of macrocyclic lactones is strongly and negatively related to all response variables. This supports previous work showing that macrocyclic lactones have negative effects on the ecology and biology of different soil invertebrate taxa, including mites, springtails, earthworms, flies, wasps (Hammer et al., ; Jochmann & Blanckenhorn, ) and dung beetles (Basto‐Estrella et al., ). These negative effects are related to the accumulation of macrocyclic lactones in cattle dung, changing their nutritional, chemical and microbiological properties (Hammer et al., ; Jochmann & Blanckenhorn, ).…”
Section: Discussionsupporting
confidence: 89%
“…This supports previous work showing that macrocyclic lactones have negative effects on the ecology and biology of different soil invertebrate taxa, including mites, springtails, earthworms, flies, wasps (Hammer et al., ; Jochmann & Blanckenhorn, ) and dung beetles (Basto‐Estrella et al., ). These negative effects are related to the accumulation of macrocyclic lactones in cattle dung, changing their nutritional, chemical and microbiological properties (Hammer et al., ; Jochmann & Blanckenhorn, ). Such contaminated dung can produce landscape‐scale toxicological effects, even at low concentrations (Jochmann & Blanckenhorn, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On-farm transmission of AMR has been characterized in the literature for a wide range of animals: pigs (Crombé et al, 2013; Novais et al, 2013), cows (Wichmann et al, 2014), and insects (Zurek and Ghosh, 2014; Usui et al, 2015; Hammer et al, 2016). A recent review of the academic literature that address the issue of antibiotic use in agriculture suggests that only seven studies (five percent) argued that there was no link between antibiotic consumption in animals and resistance in humans, while 100 (72%) found evidence of a link (O’Neill and The Review on Antimicrobial Resistance, 2015).…”
Section: Drivers Of Resistance: Antibioticsmentioning
confidence: 99%
“…Recent studies have shown that antibiotics may significantly affect the microbiota in dung and dung beetles negatively (Hammer et al 2017). In Denmark, more than half (57.1%) of the dung beetles are listed on the Danish Redlist (Department of Bioscience 2017), and one of the reasons for this may be the extensive use of antibiotics for livestock.…”
Section: Contribution Of Organic Farming To Public Goods Due To Very mentioning
confidence: 99%